Makna Kalimat Namun Aku Mengasihi Yakub Tetapi Membenci Esau Dalam Maleakhi 1:2-3 - Ananda, Bella Putri; Setyarini, Lilis; Widianto, Kasiatin (Jurnal Teologi dan Pelayanan Kerusso, 2024)
The phrase, "Yet I have loved Jacob, but Esau I have hated," found in Malachi 1:2-3, has sparked significant debate, particularly concerning the concept of election in the doctrine of salvation. Therefore, this study aims to explore the intended meaning of the author of the book of Malachi. Utilizing a qualitative exegetical method, alongside several specific analytical steps, this research seeks to produce objective findings that align with the truth of Scripture. After conducting the study through this method, it concludes that the phrase in this verse does not pertain to the concept of election in the doctrine of salvation, but rather reflects the nature of God, who is capable of both love and hatred. Furthermore, the study emphasizes that God's love and hatred cannot be equated with human emotions.